2009
DOI: 10.1111/j.1420-9101.2009.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy and phylogenetic distribution of the mammalian cecal appendix

Abstract: A recently improved understanding of gut immunity has merged with current thinking in biological and medical science, pointing to an apparent function of the mammalian cecal appendix as a safe‐house for symbiotic gut microbes, preserving the flora during times of gastrointestinal infection in societies without modern medicine. This function is potentially a selective force for the evolution and maintenance of the appendix, and provides an impetus for reassessment of the evolution of the appendix. A comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 56 publications
4
132
0
7
Order By: Relevance
“…The appendix is absent in some primates (Scott 1980). Recent studies shown, that in animals lacking an appendix the terminal part of the cecum is rich in lymphoid tissue (Smith et al 2009;Mala 2003). In many primates and mammals the appendix is much more open and sack-shaped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appendix is absent in some primates (Scott 1980). Recent studies shown, that in animals lacking an appendix the terminal part of the cecum is rich in lymphoid tissue (Smith et al 2009;Mala 2003). In many primates and mammals the appendix is much more open and sack-shaped.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have dealt with primate and mammals appendices (Scott 1980;Fisher 2000;Smith et al 2009). However, the greatest attention has been focused on well-developed rabbit appendix (e.g., Pospisil & Mage 1998;Dasso et al 2000;Hanson & Lanning 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The vermiform appendix measures a mean of 11 cm and the tip is most commonly retrocecal (74%) though the remainder have a variable location 8 .…”
Section: Important Anatomical Considerationsmentioning
confidence: 99%
“…In animals, appendicitis has been described only in anthropoid apes (7) with characteristically narrow worm-shaped appendix. On the other hand, in many primates and mammals, the appendix is much more open and sack-shaped (8).…”
Section: Introductionmentioning
confidence: 99%